Vascular Endothelial (VEGF) and Epithelial Growth Factor (EGF) as Well as Platelet‐Activating Factor (PAF) and Receptors are Expressed in the Early Pregnant Canine Uterus. Issue 1 (28th March 2012) - Schäfer‐Somi, S; Sabitzer, S; Klein, D; Reinbacher, E; Kanca, H; Beceriklisoy, HB; Aksoy, OA; Kucukaslan, I; Macun, HC; Aslan, S
Contents The aim of this study was to investigate the course of expression of platelet‐activating factor (PAF), PAF‐receptor (PAF‐R), epidermal growth factor (EGF), EGF‐R, vascular endothelial growth factor (VEGF), VEGF‐R1 and VEGF‐R2 in uterine tissue during canine pregnancy. For this purpose, 20 bitches were ovariohysterectomized at days 10–12 (n = 10), 18–25 (n = 5) and 28–45 (n = 5) days after mating, respectively. The pre‐implantation group was proven pregnant by embryo flushing of the uterus after the operation, the others by sonography. Five embryo negative, that is, non‐pregnant, bitches in diestrus (day 10–12) served as controls. Tissue samples from the uterus (placentation sites and horn width, respectively) were excised and snap‐frozen in liquid nitrogen after embedding in Tissue Tec®. Extraction of mRNA for RT‐PCR was performed with Tri‐Reagent. In the embryos, mRNA from all factors except VEGF was detected. In the course of pregnancy, significantly higher expression of PAF and PAFR as well as VEGF and VEGFR2 during the pre‐implantation stage than in all other stages and a strong upregulation of EGF during implantation were characteristic. The course of EGF was in diametrical opposition to the course of the receptor. These results point towards an increased demand for VEGF, EGF and PAF during the earliest stages of canine pregnancy.